Surface Fermi level position of hydrogen passivated Si (111) surfaces - Ristein, Jürgen; Ley, Lothar; et al. (Applied Physics Letters, 1996)
Core and valence band photoemission data of hydrogen passivated Si(111):H surfaces yield surface Fermi level positions that are indicative of a near-surface depletion layer for n- as well as p-type samples. The bulk Fermi level positions are attained after annealing at ∼400°C. These observations are explained in terms of a hydrogen induced passivation of donors and acceptors in a surface layer of the order of a μm as a result of the wet-chemical etching procedure. © 1996 American Institute of Physics.
UnivIS-Import:2015-03-05:Pub.1996.nat.dphy.IAP.exphys.surfac